(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2008)
Fluctuations of important physico-chemical parameters of a pond were investigated. Different pairs of variables had different relationships with each other by the relevant coefficients of correlation. The pH value was 7.0-7.8 and inversely related to dissolved oxygen. It is highly significant with free CO2 and CO3. Dissolved oxygen content is highly significant with water temperature, inverse relationship with free CO2, CO3 but no relationship with HCO3. The carbonate content was 9.8-12.5 ppm. The results showed significant influence of major components on the productivity of fishes in a pond. Key words : Fish, Pond ecology, Dissolved oxygen, Meteorological properties. DOI = 10.3329/bjsir.v43i3.1157 Bangladesh J. Sci. Ind. Res. 43(3), 405-410, 2008 Â